Perbandingan jumlah limfosit dan interleukin-6 setelah aerobik ringan dan sedang pada remaja - Harun, lukman (CNJ: Caring Nursing Journal, 2018)
Regular physical exercise may boost the immune system, exercise can cause physiological changes are quite large in the immune system, regular physical exercise can increase levels of Interleukin-6 and Total Lymphocyte as cytokines and adaptive defense in the immune system. This study aims to determine differences in the levels of interleukin-6, and the number of lymphocytes against mild and moderate aerobic exercise Sampling using a hypothesis test two independent groups tail with 9 people in this inklusi.Penelitian criteria using Quasi experimental design with posttest study design with Control Group. The test results comparing the levels of interleukin-6 Kruskal-Wallis test is used for the distribution of datatidak Normal. Shows that p = 0.031. This means that the average levels of IL-6 in the three groups differed significantly (p <0.05). Lymphocytes Indicate the number of test results that the results of the analysis of the test Analysis of Variance (ANOVA) showed that the value of p = 0.001. It simply means that the average number of lymphocytes in the three groups differed significantly (p <0.05).